English for Little Learners: Program Kreatif Pengenalan Literasi Bahasa Inggris bagi Anak Usia Dini - A’thi Fauzani Wisudawati; Muhyiddin Aziz; Halim Ahmad Faizin; Muhammad Isa; Yulius Harry Widodo; Ita Permatasari (Lembaga Pengembangan Kinerja Dosen, 2025)
English literacy at early childhood is a crucial foundation for language development, cognitive growth, and academic readiness. TK Desa Bagi 01, despite its high academic achievements, faces several challenges in teaching English, including a busy daily schedule, limited learning time, and restricted access to interactive learning media. This community service program was designed to address these challenges by introducing English literacy to young learners in a creative and engaging manner while simultaneously enhancing teachers’ skills in employing interactive and contextually relevant teaching media. The program employed several methods: observation of current teaching practices, planning and development of creative learning media such as flashcards, posters, storybooks, and puppets, implementation of learning activities through play-based approaches, and evaluation of student and teacher outcomes. The results indicate a significant increase in student enthusiasm, active participation, and comprehension of basic English vocabulary. Teachers also demonstrated improved creativity and confidence in using various teaching media to support literacy learning. This program shows that English literacy can be effectively fostered in early childhood using simple, locally relevant, and sustainable media. Furthermore, it highlights the importance of teacher development in enhancing the quality of English learning in rural school contexts. Overall, the initiative provides a practical model for integrating interactive English literacy education in early childhood settings with long-term potential for rural education improvement.